« Éducation » et « Politique » : enquête conceptuelle sur les limites d’une justification libérale de l’éducation au développement durable - Xavier Roth (Éducation et Socialisation)
Education for sustainable development raises one of the thorniest problems of education in general: the problem of its justification. Current research shows that most educators call for respect for individual freedoms and tolerance. But is it not paradoxical to justify by liberal values educational actions which are characterized precisely by their normative intention? In order to elucidate this paradox, we will mobilize the method of conceptual analysis. This reveals that education for sustainable development, by emphasizing the normative dimension of the general concept of « education », necessarily calls for political reflection on the nature of the good life and common good, which cannot be limited to the only liberal affirmation of respect for individual freedoms.